2020
DOI: 10.1016/j.jhep.2020.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Animal models for liver disease – A practical approach for translational research

Abstract: Animal models are crucial for improving our understanding of human pathogenesis, enabling researchers to identify therapeutic targets and test novel drugs. In the current review, we provide a comprehensive summary of the most widely used experimental models of chronic liver disease, starting from early stages of fatty liver disease (non-alcoholic and alcoholic) to steatohepatitis, advanced cirrhosis and end-stage primary liver cancer. We focus on aspects such as reproducibility and practicality, discussing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
146
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(157 citation statements)
references
References 179 publications
3
146
0
1
Order By: Relevance
“…While both CCl 4 and BDL are commonly used experimental models of advanced chronic liver disease, several differences are present among the toxic and the cholestatic models [44]. The specific immune response to each protocol may, therefore, vary to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…While both CCl 4 and BDL are commonly used experimental models of advanced chronic liver disease, several differences are present among the toxic and the cholestatic models [44]. The specific immune response to each protocol may, therefore, vary to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Basically, there are two major categories of NAFLD-related animal models: nutrient-deficient models (ie, those on a methioninecholine-deficient [MCD] diet) and those on a choline-deficient L-amino-defined diet, as well animals on a high-fat diet (HFD) and a modified HFD (adding fructose, cholesterol, trans-fats or chemicals to the HFD). 33 34 On the other hand, although HFD mimics the onset and development of NAFLD, it has limitations in the efficient induction of hepatic inflammation or fibrosis, as well as a relatively long induction time. 33,35 The disease heterogeneity that underlies the change from NAFLD to MAFLD reminds us to reflect further on whether it is reasonable to use these animal models to mimic the heterogeneous pathogenesis in human MAFLD.…”
Section: Researchers: Redirecting the Focus On Etiological Heterogementioning
confidence: 99%
“…33 34 On the other hand, although HFD mimics the onset and development of NAFLD, it has limitations in the efficient induction of hepatic inflammation or fibrosis, as well as a relatively long induction time. 33,35 The disease heterogeneity that underlies the change from NAFLD to MAFLD reminds us to reflect further on whether it is reasonable to use these animal models to mimic the heterogeneous pathogenesis in human MAFLD. Considering etiology diversity, a HFD or modified HFD in common use may mimic the only pathophysiological process of a considerable proportion of, but not all, patients with MAFLD.…”
Section: Researchers: Redirecting the Focus On Etiological Heterogementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there has been no ideal experimental model for human NASH. 45 For example, feeding of methionine and choline-deficient diet exhibits similar histopathological findings, but does not have the same mechanistic background as human NASH that is based on excess calorie intake and reduced physical activity as well as a number of genetic factors. A recent study has reported a human NASH model using pluripotent stem cell-derived organoids, 46 which sheds an insight into the cellular crosstalk between steatotic hepatocytes and monocytes as well as neighboring other types of cells.…”
Section: Dovepressmentioning
confidence: 99%